2014
DOI: 10.1021/nn502294w
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Heating Enabled by Plasmonic Nanostructures for Electrokinetic Manipulation and Sorting of Particles

Abstract: Plasmonic nanostructures support strong electromagnetic field enhancement or optical "hot spots" that are accompanied by local heat generation. This heating effect is generally seen as an obstacle to stable trapping of particles on a plasmonic substrate. In this work, instead of treating the heating effect as a hindrance, we utilized the collective photoinduced heating of the nanostructure array for high-throughput trapping of particles on a plasmonic nanostructured substrate. The photoinduced heating of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 40 publications
0
74
0
Order By: Relevance
“…26 The photothermal effects could also be combined with an AC electrical field to enable electrokinetic manipulation, allowing for microparticle sorting; this sorting was achieved by tuning the frequency of the AC field to create a strong electrothermal fluid flow, with a velocity as high as 50 lm/s. 27 Here, we demonstrate the interplay between the in-lattice micro and nanoparticle transport, driven by the near-field plasmonic forces, and the natural convection field. A simple square plasmonic optical lattice was used to confer in-lattice transport, similar to our previous work.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…26 The photothermal effects could also be combined with an AC electrical field to enable electrokinetic manipulation, allowing for microparticle sorting; this sorting was achieved by tuning the frequency of the AC field to create a strong electrothermal fluid flow, with a velocity as high as 50 lm/s. 27 Here, we demonstrate the interplay between the in-lattice micro and nanoparticle transport, driven by the near-field plasmonic forces, and the natural convection field. A simple square plasmonic optical lattice was used to confer in-lattice transport, similar to our previous work.…”
Section: Introductionmentioning
confidence: 89%
“…19,20 Cuche et al recently demonstrated that near-field optical forces can produce negative refraction effects on the trajectory of nanoparticles in a plasmonic crystal created in a patterned metallic film. 19 The same group of authors also reported on trapping and transport over a periodic array of gold nanodiscs, under illumination with a loosely Note: Paper submitted as part of the selected papers from the 5th International Conference on Optofluidics (Guest Editors: Shih-Kang Fan and Zhenchuan Yang) held in Taipei, Taiwan, July [26][27][28][29]2015. a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, novel surface-enhanced Raman scattering has greatly extended the role of the standard Raman microscope [11][12][13][14]. Commercial Raman microscopes are usually configured with metallurgical objectives that are designed to work in air.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the trapping and sorting arises from the differences between interactions of the particles with the fluid. [2][3][4][5][6][7][8] In particular, counter-rotating vortices have been used to sort particles and manipulate biopolymers. They have been used to deposit DNA precisely across electrodes 9 and trap DNA.…”
mentioning
confidence: 99%
“…Such counter-rotating vortices can be produced in microfluidic channels using acoustically driven bubbles, 3,4,30 local heating, 10 or plasmonic nanostructures. 5 The flow speed is controlled by very different external mechanisms in each case. We therefore choose a simple model to produce fluid flow that is not specific to one mechanism.…”
mentioning
confidence: 99%